Big data business innovation model for telecom operator - Jun ZHAO; Lei HUANG; Ting HUANG (Dianxin kexue, 2016)
From the perspective of some enterprises' big data value technology, despise application, value construction and despise operation problems, the importance of business innovation for big data transformation of enterprises was discussed, the characteristics of big data business innovation were analyzed and combined with the characteristics of telecom operators business and data, the big data business innovation mode suitable for telecom operators was studied, the functional framework of business innovation support system was designed, the implementation strategies and suggestions were proposed.